Transformasi digital manajemen arsip dinamis untuk mendukung tata kelola organisasi yang transparan dan akuntabel di UIN K.H. Abdurrahman Wahid Pekalongan - Muttaqin Muttaqin; Hendri Hermawan Adinugraha; Onn Bin Dato’ Md. ZIN (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2026)
Background of the Study: Effective digital records management is crucial for ensuring accountable, transparent, and efficient governance. UIN K.H. Abdurrahman Wahid Pekalongan is transitioning from a conventional system to a digital one as part of its institutional transformation. Gaps in on-the-ground implementation include the continued use of hybrid systems, limited human resource competencies, a lack of comprehensive standard operating procedures (SOPs), and weaknesses in security systems and centralized data backup availability. Objectives: This research aims to analyze the transformation of digital records management at the university, identify the factors that support and hinder it, and examine its contribution to organizational accountability. Method: This qualitative study uses an intrinsic case study approach. Data were collected through in-depth interviews with management, archivists, staff, system operators, and internal auditors, a total of eight informants. Additional data came from observations and reviews of policies, SOPs, and performance reports. Analysis followed the Miles and Huberman interactive model, with triangulation to ensure validity. Finding: The university has implemented digital archiving in phases, but still uses a hybrid system. Supporting factors include IT infrastructure and national regulations. Challenges include limited staff competencies, incomplete SOPs, and weak data security. Digital records management improves efficiency, transparency, and accountability by creating clear digital records of processes. Conclusion: Digital transformation at the university strengthens organizational accountability. Its success depends on improving staff capacity, developing clear policies, and fostering a digital mindset.